Channel Feedback Scheduling For Wireless Communications (International Journal of Engineering and Computer Science, 2013)
Opportunistic scheduling can significantly improve wireless network performance by exploiting the underlying channel condition. There has been a lot of work on opportunistic scheduling, but the problem of finding the right feedback mechanism to convey channel information has largely been untouched. In emerging multichannel systems, the per-channel feedback induces a substantial amount of feedback overhead and requires high computational complexity. To reduce the feedback overhead, we consider an opportunistic feedback strategy that activates the channel feedback opportunistically according to the channel condition. Then, we combine the opportunistic feedback with the best-n channel feedback scheme where a mobile user chooses the best n channels and transfers this information to the base station. We analyze the throughput and the amount of channel feedback information for proportionally fair opportunistic scheduling under Rayleigh fading channels. The numerical results confirm that our partial feedback schemes achieve a remarkable reduction in the amount of feedback information without significant throughput degradation, thereby saving the scarce wireless bandwidth and limited battery power.